PENGARUH NILAI-NILAI ISLAM TERHADAP TINGKAT KETERTIBAN SISWA: STUDI EMPIRIS PADA SMP MUHAMMADIYAH - Nurjanah; Sularno; Jenal Mutaqin, Dadang (LP2M JAMIAT KHEIR, 2025)
This study aims to analyze the relationship between the implementation of Islamic values and the level of student orderliness at Muhammadiyah Junior High School. The background of this research lies in the importance of character education in shaping students' orderly behavior, particularly through Islamic values, which form the foundation of Muhammadiyah educational institutions. The research method employed is a quantitative approach with a correlational design. The population consists of seventh and eighth-grade students, with a sample of 133 students selected using proportional random sampling. The research instrument used is a closed-ended questionnaire with a Likert scale. Data analysis techniques include validity and reliability tests, Pearson correlation, and simple linear regression analysis.The results indicate that both the implementation of Islamic values and the level of student orderliness are categorized as high. The Pearson correlation test shows a positive and significant relationship between the two variables, with r = 0.612 and a p-value of 0.000 (p < 0.05). The regression analysis reveals that Islamic values contribute 37.5% to students’ orderliness, while the remaining 62.5% is influenced by other factors. The study concludes that the better the implementation of Islamic values, the higher the level of student orderliness. Therefore, strengthening the internalization of Islamic values in the school environment is a crucial strategy in shaping students’ character, discipline, and moral behavior.